Part I: Iron (III)-catalyzed reactions of benzylic analogs with organosilanes & Conia-ene cyclization. Part II: Palladium (II)-catalyzed C-H functionalizations using mono-phosphoric acid directing group - Chan, Li Yan (2014)
The use of transition metals as catalyst in mediating organic reactions is inevitable. In the first part of the thesis, we discussed thoroughly the usage of cheap and environmentally friendly iron(III) catalyst in promoting reactions of (i) benzylic acetates with organosilanes; (ii) reductive dehydroxylation of benzylic alcohols with polymethylhydrosiloxane; and (iii) the Conia-ene cyclization of 2-alkynic 1,3-dicarbonyl compounds. Ample works were done which demonstrated the efficiency of iron catalyst in these areas of organic synthesis chemistry. In the second part, a novel mono-phosphoric acid directing group was used to facilitate palladium(II)-catalyzed C-H functionalization reactions, that occurred in high selectivity at the ortho-position. The phosphate directing ability was proven in (i) ortho-alkenylation; (ii) ortho-arylation; and (iii) ortho-acetoxylation of aryl hydrogen phosphates. The palladium catalytic system could tolerate a broad range of functional groups, hence making this an attractive method to synthesis valuable functionalized arenes, which are common motifs of natural products.